ADICIONES A LA AVIFAUNA DE UN CAFETAL CON SOMBRÍO EN LA MESA DE LOS SANTOS (SANTANDER, COLOMBIA) (2004)
Inventories of bird-life inhabiting shaded coffee plantations are an important step to establishing future research projects about how these kinds of agroecosystems can help to reach an equilibrium between the conservation of diversity and an appropriate exploitation of land use, given the present rates of deforestation and fragmentation of natural habitats. A characterization of the richness of bird species present in a shaded coffee plantation at La Mesa de Los Santos (Santander) was conducted from November 9th to 11th of 2003.The numbers of bird species and individuals captured were determined using mist nets at two height levels in three shaded coffee lots of different ages. Also, visual and auditory records were made in and between the lots to complement the inventory. We found that the number of species and individuals netted seems to decrease as the age of the lot increases. Seventeen new species were added to the current bird registry for the area, three of which are new for the migratory bird species listed as inhabiting coffee lands in the country. We conclude that the shaded coffee plots studied are an appropriate habitat to maintain migratory as well as resident bird species, and that the use of mist nets at high levels makes it possible to record some species that can’t be captured in any other way.